EСONOMIC AND MONETARY UNION: CORRECTION ОF FAILURES - A. N. Tsibulina (Vestnik MGIMO-Universiteta)
The articles deals with the initial design failures of the European and Monetary Union which could have lead to the current sovereign debt crisis of some of its member-states. It touches upon issues such as the Theory of Optimum Currency Areas, economic imbalances and situation with the public finances within the EU. The EU makes efforts to implement new initiatives which could prevent the euro area from future crises while debates remain on the best possible options. These initiatives imply not only deepening of economic integration but also of a political one. Under these circumstances reaching a consensus in EU- 27 becomes quite a challenging process and different groupings of countries might appear and this can even more complicate decision-making and functioning of the EU. While the outcome of the reforms is still to be seen in the future, some macroeconomic indicators show that real adjustment process has started in the periphery countries due to urgent measures taken at the EU level. Nonetheless the latter ones have not yet generated what is necessary for a sustained way out of the crisis.